Breaking through? Exploring care in the early life of elite Swedish athletes - Kjær, J. B.; Bjärsholm, D.; Fahlström, P. G.; Linnér, S. (Sports Coaching Review, 2023)
Through retrospective interviews with 14 Swedish elite athletes, this qualitative study explores care among the early life of elite athletes. Using Nel Noddings` care theory as a framework for the data, the study considers caring practices from significant others in the micro-environment of the emerging elite athlete. Athletes highlight the natural care they received as children from their parents and the ethical care they received by their coaches as instrumental in their athletic upbringing, especially during the junior to senior level transition. Consequently, we suggest ethical care supplements natural care. This paper also introduces Noddings` concept of practice and discusses opportunities and challenges in the coach-athlete relationship based on caring. Implications of this study problematise the role sport organisations play in supporting natural and ethical care among stakeholders in the micro-environment.